2017
DOI: 10.1016/j.celrep.2017.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Carbohydrate Response Element Binding Protein in Adipocytes Causes Systemic Insulin Resistance and Impairs Glucose Transport

Abstract: Summary Lower adipose-ChREBP and de novo lipogenesis (DNL) are associated with insulin resistance in humans. Here we generated adipose-specific ChREBP knockout (AdChREBP KO) mice with negligible sucrose-induced DNL in adipose tissue (AT). Chow-fed AdChREBP KO mice are insulin-resistant with impaired insulin action in liver, muscle and AT, and increased AT inflammation. HFD-fed AdChREBP KO mice are also more insulin-resistant than controls. Surprisingly, adipocytes lacking ChREBP display a cell-autonomous reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 34 publications
6
132
1
Order By: Relevance
“…In fact, adipose‐specific ChREBP knockout mice exhibit hyperinsulinemia, adipose tissue inflammation and impaired glucose transport and these mice have lower PAHSAs levels in serum and adipose tissue. Supplementation of adipose‐specific ChREBP knockout mice with 9‐PAHSA prevents all these alterations . At least, 12/13 and 5‐PAHSA serum levels were reduced in obese wild type mice but, on the contrary, they were increased in high‐fat diet aP2‐WisP2 trangenic mice with WISP2 a recently identified adipokine, highly expressed in the adipose tissue.…”
Section: Fahfas Are Endogenous Lipidsmentioning
confidence: 99%
“…In fact, adipose‐specific ChREBP knockout mice exhibit hyperinsulinemia, adipose tissue inflammation and impaired glucose transport and these mice have lower PAHSAs levels in serum and adipose tissue. Supplementation of adipose‐specific ChREBP knockout mice with 9‐PAHSA prevents all these alterations . At least, 12/13 and 5‐PAHSA serum levels were reduced in obese wild type mice but, on the contrary, they were increased in high‐fat diet aP2‐WisP2 trangenic mice with WISP2 a recently identified adipokine, highly expressed in the adipose tissue.…”
Section: Fahfas Are Endogenous Lipidsmentioning
confidence: 99%
“…Thus, increased hepatic ChREBP expression can dissociate hepatic steatosis from IR, with improvements in both lipid and glucose homeostasis [71] . Second, a second ChREBP isoform, ChREBPβ, that predicts insulin sensitivity, has been identified in white adipose tissue, and the loss of adipose-ChREBP was shown to be sufficient to cause insulin resistance in mice [72,73] . Third, FA binding protein 4 (FABP4)-Cre mediated expression of constitutively active ChREBP in mice was shown to improve insulin sensitivity and glucose tolerance in response to HFD challenge [74] .…”
Section: Both Curcumin and Insulin Stimulate Hepatic Chrebp Expressionmentioning
confidence: 99%
“…As a result, when Pflimlin et al report that endogenous PAHSA levels are below the limit of quantitation in serum of mice fed the hydrogenated vegetable diet with which we detect quantifiable serum levels, it most likely reflects limitations in their methodology. We (Yore et al, 2014; Vijayakumar et al, 2017; Syed et al, 2018) and others (Brezinova et al, 2018) also detect PAHSA levels in serum of chow-fed mice and some isomers are higher than in HFD-fed mice. In contrast, Pflimlin et al found levels to be below the limit of detection in mice on several LFDs, including the chow diet we used.…”
Section: Lc-msmentioning
confidence: 52%
“…Thus, no conclusions can be drawn from their in vitro studies regarding whether PAHSAs augment insulin sensitivity. Differences in the incubation time with PAHSAs could also contribute to the different results, although we have seen effects with incubation times ranging from 2.5 hr (Vijayakumar et al, 2017) to 6 days (Yore et al, 2014) (Table S1). …”
Section: In Vitro Experimentsmentioning
confidence: 96%
See 1 more Smart Citation